Short-chain fatty acids directly exert anti-inflammatory responses in podocytes and tubular epithelial cells exposed to high glucose - Li, Yan Jun; Ma, Jin; Loh, Yik Wen; Chadban, Steven J.; Wu, Huiling (Frontiers in Cell and Developmental Biology, 2023)
Aims: Gut-microbiome derived short-chain fatty acids exert anti-inflammatory effects and delay progression of kidney disease in diabetic nephropathy. The aim of this study was to examine the impact in vivo and in vitro of short-chain fatty acid treatment on cellular pathways involved in the development of experimental diabetic nephropathy. Methods: To determine the effect of short-chain fatty acids in diabetic nephropathy, we compared wildtype, GPR43−/− and GPR109A−/− mice diabetic mice treated with acetate or butyrate and assessed variables of kidney damage. We also examined the impact of short-chain fatty acid treatment on gene expression in renal tubular cells and podocytes under high glucose conditions. Results: Short-chain fatty acid treatment with acetate or butyrate protected wild-type mice against development of diabetic nephropathy, exhibiting less glomerular hypertrophy, hypercellularity and interstitial fibrosis compared to diabetic controls. Acetate and butyrate treatment did not provide the same degree of protection in diabetic GPR43−/− and GPR109A−/− diabetic mice respectively. Consistent with our in vivo results, expression of pro-inflammatory genes in tubular epithelial cells exposed to high glucose were attenuated by acetate and butyrate treatment. Acetate did not reduce inflammatory or fibrotic responses in glucose stimulated GPR43−/− TECs. Butyrate mediated inhibition of pro-fibrotic gene expression in TECs through GPR109A, and in podocytes via GPR43. Conclusion: SCFAs protect against progression of diabetic nephropathy and diminish podocyte and tubular epithelial injury and interstitial fibrosis via direct, GPR-pathway dependent effects on intrinsic kidney cells. GPR43 and GPR109A are critical to short-chain fatty acid mediated reno-protection and have potential to be harnessed as a therapeutic target in diabetic nephropathy.